IMPROVING THE AGING QUALITY OF LIFE IN WANG MAN SUB-DISTRICT, WAT SING DISTRICT, CHAINAT PROVINCE - Singsorm, Patthana; Sungpanich, Piyajit; Saisena, Natthapat; Khamthongthip, Tawat; Ratthapat, Suthathip (Journal of MCU Nakhondhat, 2023)
The objectives of this research were 1) to study the quality of life of the elderly in Wang Man Subdistrict, Wat Sing District, Chai Nat Province, 2) to survey the population data of the elderly, and 3) to create an integrated Buddhist quality of life development model of the elderly. This is a mixed methods research consisting of quantitative and qualitative research. The sample was elderly people in Wang Man Subdistrict, Wat Sing District, Chai Nat Province from 8 villages. Yamane's calculated sample size was determined and a 90% confidence level was achieved for 88 people. Research tools include questionnaires, semi-structured interviews, quantitative data analysis for frequency, percentage, mean and standard deviation. Qualitative studies used the instrument of semi-structured questionnaires and collected data with group discussions and in-depth interviews. Analyze data with content analysis and quality check with triangular techniques. The research found that 1) the life quality according to the 6 main measures, they mostly were supported good help from the officers in charge of the aging in trouble, informed news about the religious activities, provided the occupational groups for the aging, respected by the relatives and family members, provided the information area for the aging such as community hall, public broadcast tower, 2) for supporting the development of the aging’s quality of life found that they ate the food which is good for health, did the useful things for their village, participated in the religious activities, and applied sufficiency economy for earning a living, and 3) the model of the aging quality of life created in form of the activity titled “The Way of Life through Simple Path in the New Normal” by applying eightfold path; right view, right resolve, right speech, right conduct, right livelihood, right effort, right mindfulness, and right samadhi to daily life was implemented.